Efficacy of Neuroendoscopic Treatment for Septated Chronic Subdural Hematoma - Deng, Jianhong; Wang, Fangyu; Wang, Haojie; Zhao, Mingpei; Chen, Guorong; Shangguan, Huangcheng; Yu, Lianghong; Jiang, Changzhen; Fang, Wenhua; Yao, Peisen; Kang, Dezhi; Zheng, Shufa (Frontiers in Neurology, 2022)
Objective: Neuroendoscopic treatment is an alternative therapeutic strategy for the treatment of septate chronic subdural hematoma (sCSDH). However, the safety and efficacy of this strategy remain controversial. We compared the clinical outcomes of neuroendoscopic treatment with those of standard (large bone flap) craniotomy for sCSDH reported in our center. Furthermore, the safety and efficacy of the neuroendoscopic treatment procedure for sCSDH were evaluated. Methods: We retrospectively collected the clinical data of 43 patients (37 men and six women) with sCSDH who underwent either neuroendoscopic treatment or standard (large bone flap) craniotomy, such as sex, age, smoking, drinking, medical history, use of antiplatelet drugs, postoperative complications, sCSDH recurrence, length of hospital stay, and postoperative hospital stay. We recorded the surgical procedures and the neurological function recovery prior to surgery and 6 months following the surgical treatment. Results: The enrolled patients were categorized into neuroendoscopic treatment (n = 23) and standard (large bone flap) craniotomy (n = 20) groups. There were no differences in sex, age, smoking, drinking, medical history, antiplatelet drug use, postoperative complications, and sCSDH recurrence between the two groups (p > 0.05). However, the patients in neuroendoscopic treatment group had a shorter length of total hospital stay and postoperative hospital stay as compared with the standard craniotomy group (total hospital stay: 5.26 ± 1.89 vs. 8.15 ± 1.04 days, p < 0.001; postoperative hospital stay: 4.47 ± 1.95 vs. 7.96 ± 0.97 days, p < 0.001). The imaging and Modified Rankin Scale at the 6-month follow-up were satisfactory, and no sCSDH recurrence was reported in the two groups. Conclusions: The findings of this study indicate that neuroendoscopic treatment is safe and effective for sCSDH; it is minimally invasive and could be clinically utilized.